ANALISIS PENGARUH KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2014 - ASTARI, GENIS (Jurnal Akuntansi AKUNESA, 2015)
This research aimed to analyze the influence of institutional ownership on earnings management. Institutional ownership is calculated from the amount of shares owned institution per amount of shares outstanding. Discretionary accrual is the proxy of earning management. This research used 38 banking companies listed in Indonesia Stock Exchange, selected using purposive sampling method, during the research period 2013-2014. Data were analyzed using simple regression method. Based on test results concluded that institutional ownership variable has no significant effect on earnings management. This means that companies with high institutional ownership does not guarantee can minimize earnings management practices at the company.Keywords: earnings management, good corporate governance, institutional ownership.